2018
DOI: 10.1097/der.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Genital Allergic Contact Dermatitis

Abstract: Genital allergic contact dermatitis (ACD) is an uncommon disorder, yet it severely impairs the quality of life for both men and women. Because of cultural taboos, many patients self-treat and delay proper diagnosis before presenting to a provider. Diagnosis is further confounded by irritant contact dermatitis and other genital dermatoses, which can predispose to skin barrier dysfunction and allergen penetration. Genital ACD can present acutely with erythematous erosions and pruritus or chronically with licheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…19 Moreover, as the higher frequency of iatrogenic contact dermatitis is observed in the genitalia, 23 clinicians and patients should always be careful when using topical preparations containing anesthetics, antibiotics, corticosteroids, fragrances, and preservatives, which are strongly associated with genital sensitization. 24,25 In this study, we found a relatively high prevalence of genital eczema in patients with AD. However, besides genital eczema, infections and diverse chronic inflammatory skin diseases must be considered as differential diagnoses.…”
Section: Discussionsupporting
confidence: 51%
“…19 Moreover, as the higher frequency of iatrogenic contact dermatitis is observed in the genitalia, 23 clinicians and patients should always be careful when using topical preparations containing anesthetics, antibiotics, corticosteroids, fragrances, and preservatives, which are strongly associated with genital sensitization. 24,25 In this study, we found a relatively high prevalence of genital eczema in patients with AD. However, besides genital eczema, infections and diverse chronic inflammatory skin diseases must be considered as differential diagnoses.…”
Section: Discussionsupporting
confidence: 51%
“…Many studies found a significant number of patients with genital ACD to be allergic to fragrance mix I or balsam of Peru [11,14,17,[22][23][24].…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%
“…Dermatite axilar é relatada por MI presente em desodorantes, na qual as pregas cutâneas dessa região facilitam a penetração e sensibilização, de modo similar ao que ocorre na região anogenital 1 . Eczema perianal causado pela exposição à MCI/MI e MI em lenços umedecidos é bem reportada 16 . Uma das primeiras recomendações feita por generalistas em casos de prurido anal é iniciar o uso de lenços umedecidos para melhorar a higiene.…”
Section: Aspectos Clínicosunclassified